Perceived transformational leadership, instructor behaviors, and motivation to learn: A mediated model - Smy, Victoria; Shelton, Katherine; Tombs, Michael; Patrick, John (CAIRN, 2016)
Motivation to learn is an important determinant of various indicators of training effectiveness, such as improved satisfaction with training, higher self-efficacy, greater intent to transfer trained skills, and improved declarative knowledge (Colquitt, LePine, & Noe, 2000). Similarly, transformational leadership improves employee attitudes and performance, largely through its motivational effects (Bass, 1999). However, surprisingly little research addresses whether transformational instructor behavior, in training contexts, impacts upon training-related attitudes, and therefore also influences subsequent training success. A model was developed concerning associations between perceived transformational instructor behaviors and trainee attitudes, including motivation to learn. Measurement and structural models were assessed using data from 578 UK military recruits undergoing phase one of recruit training. Results indicate that trainee perceptions of their instructor’s transformational leadership behaviors were positively associated with motivation to learn. Instructor transformational leadership was also positively associated with trainee attitudes concerning instrumentality (Mathieu, Tannenbaum, & Salas, 1992) and valence (the desirability of doing well within the training context, Colquitt & Simmering, 1998), with these attitudes partially mediating the association between instructor transformational leadership and motivation to learn. Cross-validation of the model using 371 different trainees in the more specialized phase of recruit training revealed the same pattern of significant associations. These findings have theoretical implications for models of training motivation, which need to incorporate perceptions of transformational instruction. In addition, present results have practical implications as interventions aimed at training instructors to more effectively adopt transformational behaviors should be used to improve the motivation of trainees, and there is evidence to suggest that individuals can be trained to demonstrate greater transformational leadership (e.g., Dvir, Eden, Avolio, & Shamir, 2002).